The Role of Multiple Christian Religious Education in Building Multicultural Community Unity: Peran Pendidikan Agama Kristen Majemuk dalam Membangun Persatuan Masyarakat Multikultural - Mesirawati Waruwu; Christian Pungky Wijanarko; Mariani Harmadi (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
This article formulates the role of Christian Religious Education in a pluralistic society in realizing unity which is part of the practice of Pancasila, especially the 3rd principle, namely Indonesian Unity. Indonesia is a country that is prone to conflicts that arise from the diversity of culture, race, ethnicity, language and religion that threatens the unity and integrity of the nation if not handled properly. Pancasila as an ideology contains an important function of regulating people's lives in the nation and state, especially the third principle, namely the unity of Indonesia. The method used is library research or library research. The results of this study encourage the spirit to build unity and integrity in a pluralistic society with the starting point coming from understanding the direction, mission, The vision and goals of Christian Religious Education are plural so that it creates a personal commitment to apply Christian values starting from the scope of the community such as families, schools and communities both locally and globally. On this basis, the role of Christian Religious Education is expected to be able to contribute to realizing the ideals of Indonesia through the process of character building, morals, morals and the practical inculcation of Pancasila values in the life of Indonesian society.